KOMUNIKASI ANTAR KELUARGA MUSLIM BEDA BUDAYA DI PALANGKA RAYA - Ngalimun Ngalimun; Rahmawati Rahmawati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This study aims to determine the model of communication between Muslim families of different cultures and inhibiting factors of communication. This research was conducted on couples of five families who married with different cultures in the Tanjung Pinang sub-district, Pahandut sub-district, Palangka Raya City. With the marriage of different cultures is expected to enrich the culture and can also be used as lessons for individuals who want to do the marriage. This type of research is descriptive qualitative, the sample of this study is 5 families. The communication model of 5 Muslim families with different cultures can be seen from the adaptation process that occurs in their respective families. In adapting there are various things that start from the adaptation of the language, through habits, through different food tastes and complement each other so that each family has a different communication model. Whereas the factors which hamper communication in the family are the difficulty of language adjustment, the existence of prejudice, the communication that occurs is one- way or there is no feedback and errors in the evaluation of the message delivered.